The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s40726-016-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Elements in the Soil Environment

Abstract: Rare earth elements (REE) are a homogenous group of 17 chemical elements in the periodic table that are key to many modern industries including chemicals, consumer electronics, clean energy, transportation, health care, aviation, and defense. Moreover, in recent years, they have been used in agriculture. One of the consequences of their worldwide use is the possible increase of their levels in various environmental compartments. This review addresses major topics concerning the study of REE in the soil environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(145 citation statements)
references
References 149 publications
3
121
0
Order By: Relevance
“…In those particular studies, measurements of REEs were performed on P. ostreatus and C. cylindracea mushrooms derived from substrates consisting of wheat‐straw and sawdust from Poland and China respectively. Especially as regards China, i.e, the country with the largest REE reserves and the biggest producer in the world, REEs are used to enrich fertilizers, which are then widely applied in agriculture in continuously increasing amounts . This expanding use of REEs in various fields of human activity could progressively affect their occurrence in living organisms with unknown long‐term repercussions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In those particular studies, measurements of REEs were performed on P. ostreatus and C. cylindracea mushrooms derived from substrates consisting of wheat‐straw and sawdust from Poland and China respectively. Especially as regards China, i.e, the country with the largest REE reserves and the biggest producer in the world, REEs are used to enrich fertilizers, which are then widely applied in agriculture in continuously increasing amounts . This expanding use of REEs in various fields of human activity could progressively affect their occurrence in living organisms with unknown long‐term repercussions.…”
Section: Resultsmentioning
confidence: 99%
“…Especially as regards China, i.e, the country with the largest REE reserves and the biggest producer in the world, REEs are used to enrich fertilizers, which are then widely applied in agriculture in continuously increasing amounts. 38 This expanding use of REEs in various fields of human activity could progressively affect their occurrence in living organisms with unknown long-term repercussions. On the other hand, it is noteworthy that REE concentration values found in C. cylindracea and P. ostreatus mushrooms (in this study) are quite similar to those previously reported from measurements on wild mushrooms, [12][13][14]39 and differ only when compared to samples collected alongside a heavily trafficked road in Poland (where much higher values were observed for most elements).…”
Section: Concentration Of Rees In Mushroomsmentioning
confidence: 99%
“…Cerium and other rare earths (REs) have the potential to accumulate progressively in soil due to their increased use in a variety of modern industries and in the last 30 years their wide use as fertilizers in Chinese agriculture (Hu et al, 2004;Tyler, 2004;El-Ramady, 2010;Emsley, 2011;Ramos et al, 2016). Due to elevated concentrations of REs in phosphate fertilizers, Ce can accumulate in agricultural soils outside China too (Kanazawa and Kamitani, 2006;Ramos et al, 2016). For example, it has been estimated that in Brazilian soils 12,000 t of Ce were added through phosphate fertilizers in 2014 (Ramos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to elevated concentrations of REs in phosphate fertilizers, Ce can accumulate in agricultural soils outside China too (Kanazawa and Kamitani, 2006;Ramos et al, 2016). For example, it has been estimated that in Brazilian soils 12,000 t of Ce were added through phosphate fertilizers in 2014 (Ramos et al, 2016). However, the increase of REs in soil is usually small and large amounts are easily washed away Science of the Total Environment 593-594 (2017) [735][736][737][738][739][740][741][742][743][744] from upper soil horizons through rain of watering (Tyler, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nutrients in ash has the potential to fertilize and to correct soil acidity (Melese et al, 2015). In this context, studies are needed to understand the composition of the ash, and to determine the proper quantities and the effects of ash applied to the soil, subsoil, plants, feasibility of use (Ramos et al, 2016), and effects on water in the subsoil. On the other hand, indiscriminate or excessive use of the ash may cause problems (Quirantes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%